Developing intercultural competence in practice - Byram, Michael; Nichols, Adam; Stevens, David, 1952- (Languages for intercultural communication and education ;, 2001)
It is now widely recognised that learning a language should not just involve linguistic competence but also intercultural competence. It is also clear that intercultural competence can be developed through related subjects such as geography, history, mother tongue teaching. This book takes this as a given and provides practical help for teachers who wish to help their learners acquire intercultural competence in the ordinary classroom. It contains descriptions of lessons and materials from a wide range of classrooms in several countries and for beginners to advanced learners.